2005
DOI: 10.1203/01.pdr.0000147734.53277.75
|View full text |Cite
|
Sign up to set email alerts
|

Systolic and Diastolic Ventricular Function Assessed by Pressure-Volume Loops in the Stage 21 Venous Clipped Chick Embryo

Abstract: Cardiac pressure-volume relations enable quantification of intrinsic ventricular diastolic and systolic properties independent of loading conditions. The use of pressure-volume loop analysis in early stages of development could contribute to a better understanding of the relationship between hemodynamics and cardiac morphogenesis. The venous clip model is an intervention model for the chick embryo in which permanent obstruction of the right lateral vitelline vein temporarily reduces the mechanical load on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…During cardiovascular development initially, periostin is expressed in response to signaling from the BMP and TGF-␤ family of growth factors (Horiuchi et al, 1999;Ji et al, 2000;Hall et al, 2001;Kruzynska-Frejtag et al, 2001Lindner et al, 2004). However, as development progresses, the heart must withstand the increasing influence of hemodynamic sheer stress (Stekelenburg et al, 2004). Thus, we might predict an increase of periostin within the valvular apparatus and the walls of the outflow tract, structures that also undergo tension and mechani- Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During cardiovascular development initially, periostin is expressed in response to signaling from the BMP and TGF-␤ family of growth factors (Horiuchi et al, 1999;Ji et al, 2000;Hall et al, 2001;Kruzynska-Frejtag et al, 2001Lindner et al, 2004). However, as development progresses, the heart must withstand the increasing influence of hemodynamic sheer stress (Stekelenburg et al, 2004). Thus, we might predict an increase of periostin within the valvular apparatus and the walls of the outflow tract, structures that also undergo tension and mechani- Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We showed that already during embryonic development, patterning of KLF2 gene expression relates to areas of high shear stress (Groenendijk et al, 2004;Vennemann et al, 2006). Experimental changes in embryonic blood flow lead to changes in gene expression patterning of KLF2, ET1, and eNOS (Groenendijk et al, 2005), and lead to loss of proper cardiovascular function (Stekelenburg-de Vos et al, 2005Ursem et al, 2004) and the development of structural anomalies (Hogers et al, 1997(Hogers et al, , 1999. We have recently identified the inverse correlation between the expression of KLF2 and the presence of endothelial primary cilia in the embryonic heart (Van der Heiden et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Besides these morphological anomalies, hemodynamic defects have also been demonstrated, showing a decrease in heart rate and an increase in mean dorsal aortic blood flow (11). Hemodynamic changes occur immediately after venous clipping (124) but also have long-term effects, including increased ventricular stiffness due to reduced contractility and reduced compliance (123,135), as demonstrated with pulsed echo-Doppler analyses and videoscopically determined pressurevolume loops. The effects are demonstrated even extending to several days after the clip challenge (reviewed in Ref.…”
Section: Cardiac Malformationsmentioning
confidence: 99%